Rumah Tahu Mandiri Energi (RTME): New pattern on tofu production without fossil fuel consumption in Sentra Tahu Cibuntu, Bandung, West Java - Agus Ramelan; Usup; Novia Anggraeni (The International Journal of Management Science and Information Technology (IJMSIT), 2015)
The main background of this research was the high dependency on conventional fuel oil i.e. LPG in tofu industry at Sentra Tahu Cibuntu, Bandung. Author had studied and explored the idea and potency of biogas based on tofu liquid waste (whey) as the substitute of LPG by designing the prototype which was named Rumah Tahu Mandiri Energi (RTME) model. The methods that we applied for this research were experimental research and literature. The expected results were that the potency of tofu waste to be processed into biogas has a very good prospect, guide book of how to make biogas for the tofu producer, prototype of Rumah Tahu Mandiri Energi as basic study effort of the implementation of tofu waste biogas has been made and the community of Sentra Tahu Cibuntu shown good responds regarding the model of RTME.
Keywords: 650; whey; biogas; rumah tahu mandiri energi (rtme)